Postpartum Psychosis Presented with Catatonia: A Case Report - Mahdiyeh Verdipour; Fariborz Rezaie Talab; Mona Asadi; Fariba Zemorshidi (Mashhad University of Medical Sciences, 2018)
Introduction: Catatonia is a neuro-psychological syndrome characterized by motor, behavioral, emotional, and vegetative symptoms. This phenomenon can occur in primary psychological disorders and in association with neurological and other general medical diseases. Postpartum catatonia is a rare condition. In this research, we reviewed the presentation, diagnosis, and treatment of a case of postpartum psychosis with catatonia. Case presentation: A 21-year-old woman was presented with mutism, waxy flexibility, unresponsiveness and fever 10 days after delivering a healthy neonate. Assessments were made to exclude meningoencephalitis and other possible underlying medical disorders. After the investigations, a perinephric abscess was found in abdominal sonography. Despite the percutaneous abscess drainage, antibiotic therapy and treatment of fever, other symptoms continued. After catatonia diagnosis, the patient was treated with oral lorazepam, which significantly improved the signs of this disease. However, appearance of psychotic signs (e.g., delusions, hallucinations, and suicide thoughts) led to the diagnosis of postpartum psychosis and treatment of the patient with antipsychotic medications. Furthermore, she was candidate of electroconvulsive therapy to accelerate the pace of recovery. The patient responded dramatically to electroconvulsive therapy.   Conclusion: Catatonia is a rare complication of medical and psychological disorders, which can be seen in postpartum period. Early diagnosis and treatment of postpartum catatonia is crucial for maternal and neonatal health.